Lean MASLD and IBD: Exploring the Intersection of Metabolic Dysfunction and the Gut–Liver Axis - Adrian Rotaru; Remus Stafie; Ermina Stratina; Sebastian Zenovia; Robert Nastasa; Horia Minea; Laura Huiban; Tudor Cuciureanu; Cristina Muzica; Stefan Chiriac; Irina Girleanu; Ana-Maria Singeap; et al. (Life)
Metabolic dysfunction-associated steatotic liver disease (MASLD) challenges traditional paradigms by manifesting in lean individuals. The link between MASLD and inflammatory bowel disease (IBD) underscores the importance of the gut–liver axis in disease progression and chronic inflammation. This study evaluates MASLD prevalence, clinical characteristics, and diagnostic predictors in lean individuals with and without IBD. This prospective study included 387 lean patients. Hepatic steatosis and fibrosis were assessed using vibration-controlled transient elastography (VCTE). Anthropometric, clinical and biological data were compared. The subgroup analyses focused on MASLD patients with and without IBD. MASLD was present in 34.1% of lean individuals and 46.3% of those who were lean with IBD. MASLD patients had increased visceral adiposity (CUN-BAE: 31.21 ± 5.42 vs. 24.57 ± 6.49, p < 0.001) and metabolic dysfunction, including dyslipidemia and elevated fasting glucose. IBD-MASLD patients exhibited greater hepatic steatosis and systemic inflammation. CUN-BAE outperformed FLI and HSI in predicting liver steatosis, especially in IBD patients (AUC = 0.806). Lean MASLD, particularly in IBD patients, highlights the need for tailored diagnostic and management strategies. The gut–liver axis plays a key role in disease progression, and the CUN-BAE index demonstrates superior accuracy for identifying liver steatosis.